2010
DOI: 10.1007/s12355-010-0035-3
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Stress in Sugar Beet

Abstract: The production of sugar beet (Beta vulgaris L.) is often limited by environmental conditions that cause decreased rates of photosynthesis, canopy expansion, root growth and sucrose accumulation. These conditions include insufficient water, heat, freezing temperatures and salinity. Compared to other crops such as cereals, harvestable sugar yields can be obtained even under harsh growing conditions. However, the realization of maximum production efficiency and profits demands that varieties must show less suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 38 publications
1
30
0
1
Order By: Relevance
“…In many regions where sugar beet production is largely dependent on rainfall, yield losses due to drought are common (Ober and Rajabi 2010). Compared with other crops, although sugar beet is relatively tolerant to drought, it is very sensitive to drought during the seedling stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many regions where sugar beet production is largely dependent on rainfall, yield losses due to drought are common (Ober and Rajabi 2010). Compared with other crops, although sugar beet is relatively tolerant to drought, it is very sensitive to drought during the seedling stage.…”
Section: Introductionmentioning
confidence: 99%
“…The most likely solution is to improve the drought tolerance of sugar beet varieties and, for the longer term, efforts are underway to find drought-tolerant genotypes (Ober et al 2004(Ober et al , 2005. Furthermore, there is a wide range of genotypic variability for drought tolerance in sugar beet germplasm (Ober and Rajabi 2010;Romano et al 2013). Therefore, it is necessary to evaluate the drought tolerance of local commercial sugar beet cultivars in the seedlings stage.…”
Section: Introductionmentioning
confidence: 99%
“…Wild beet was already used for sugar beet genetic improvement against pathogens (Panella and Lewellen, 2007). While its potential for improvement against abiotic factors has not yet been exploited, it has been proposed that the ability to accumulate compatible solutes is a breeding goal for abiotic stress tolerance (Bagatta et al, 2008; Ober and Rajabi, 2010; Wu et al, 2014), as well as the ability to accumulate Na + and K + (Abbasi et al, 2015). Europe is one of the most important centers for beet diversity (Maxted et al, 2008), the Iberian Peninsula being considered one center of origin of the Beta complex (OECD, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In sugarbeet, drought tolerance research has been limited because the extent of the problem of water stress was not fully comprehended; there were thought to be few differences among cultivars, and it was difficult to design appropriate selection methods in breeding programs (Ober et al, 2004;Ober and Rajabi, 2010). However, limited research has shown that there exists a large variation in sugarbeet yield and quality due to drought tolerance within commercial sugarbeet cultivars (Bloch and Hoffmann, 2005;Ober et al, 2004;Pigeon et al, 2006).…”
mentioning
confidence: 99%
“…The ideal drought tolerant genotype would be one with the highest intercept (highest yield under lowest water input) and lowest slope (lowest sensitivity to water deficits) (Cattivelli et al, 2008). These relationships have been utilized to assess drought tolerance in sugarbeet (Pidgeon et al, 2006;Ober and Rajabi, 2010), and differences among hybrids have been found to exist. Another common method of identifying plant hybrids that have yield stability under limited water conditions is the drought susceptibility index (DSI, Siahpoosh et al, 2011).…”
mentioning
confidence: 99%